Literacy of Suicide among Doctors and Nurses at a Tertiary Care Hospital in Nepal - Shah, Sunil; Neupane, Dipendra; Sah, Kamlesh Kumar (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Increased knowledge and improved attitudes about suicide are important factors for suicide-prevention strategies. Not only mental health professionals and public, but doctors and nurses working in other departments and general hospitals, especially in resource limited low-middle income country like Nepal, need to be knowledgeable identifying and making appropriate referrals for mental health issues and suicidal patients. This study was conducted to assess doctors and nurses’ literacy of suicide at a tertiary care government center in Nepal. Methods: A descriptive cross-sectional questionnaire-based study was conducted among doctors and nurses working at the hospital. Literacy of suicide scale was utilized to assess the status of literacy regarding suicide among 188 study participants. Descriptive statistics were applied. Results: The total mean literacy of suicide scale (LOSS) score was calculated to be 13.07 (SD=3.65). Higher number of participants, 117 (62.2%) scored above mean on total LOSS score. Performance was the poorest on recognizing the signs of suicide while it was best on identifying the cause of suicide. People with relationship problems or financial problems have a higher risk of suicide was correctly identified by 89.9% of the participants. While only 60 (31.9%) participants correctly answered item “men are more likely to suicide than women” from the domain risk. Conclusions: Majority of nurses and doctors performed better on the literacy of suicide scale. Health professionals were found knowledgeable about suicide. Those with higher level of education, specialization and training in mental health scored higher. Future studies among various categories of population and association of level of literacy and attitude, practices is needed.